Estudo fitoquímico de folhas e galhos de Cheiloclinium cognatum (Celastraceae) e síntese de derivados glicosiltriazólicos de triterpenos pentacíclicos com potencial citotóxico - Rafael Cesar Gonçalves Pereira (2021)
Cheiloclinium cognatum is a Celastraceae species, typical of Brazilian Cerrado, and rich in pentacyclic triterpenes. Leaves and branches of this plant were studied and led to the identification of 17 constituents. Among them, two fatty compounds (triacylglycerol and fatty acid), a steroid (β-sitosterol), a triterpene fatty ester (3β acyloxyurs-12-ene), nine pentacyclic triterpenes, six of which are friedelanes (friedelin, friedelinol, canophyllol, 29-hydroxyfriedelan-3-one, friedelane-3β,29-diol and 3-oxofriedelan-29-yl acetate), a glutinane (glutinol), an ursane (α-amyrin) and an oleanane (β-amyrin), a flavonoid (epigallocatechin), two phenolic acids (vanillic and syringic acids) and a xanthone (mangiferin) were obtained. The synthesis, in three stages, of ten new glycosidic triazole triterpenoids was also carried out, starting from a mixture of 29-hydroxyfriedelan-3-one and friedelane-3β,29-diol. The cytotoxic activity for natural products obtained from C. cognatum as well as for synthetic products was evaluated against two leukemia tumor cell lines, THP-1 and K562. The first corresponds to acute myeloid leukemia cells and the second to chronic myeloid leukemia. All assayed natural products exhibited moderate to high cytotoxic activity when compared to positive controls, with emphasis on friedelinol, α-amyrin and 3-oxofriedelan-29-yl acetate, which presented IC50 equal or lower and selectivity indexes equal or greater than controls. In regard of the synthetic products, two intermediates, populnonic acid and N-propargylpopulnonamide, showed IC50 similar to the positive control for the K562 strain. A glycosidic triazole derivative, (1(2,3,4,6-tetra O-acetyl-1-deoxy-α-L-fucopyranosyl)1,2,3-triazole-4-yl)methyl populnonate, showed moderate activity compared to the controls for the two strains tested. The triterpenes friedelinol and α-amyrin had their mechanisms of action evaluated. The results suggested that the apoptosis was due to the activation of intrinsic mitochondrial pathway, evidenced by the positive regulation of BAK mRNA expression. Chemometric studies indicated that their activities may be related to molecular size and shape, as well as to the electronic interactions of the hydroxyl group at the C-3 position and specific molecular targets.